MitomiRs: their roles in mitochondria and importance in cancer cell metabolism - Renčelj, Andrej (Radiology and oncology (Ljubljana), 2021)
Background. MicroRNAs (miRNAs) are short non-coding RNAs that play important roles in almost all biological path- ways. They regulate post-transcriptional gene expression by binding to the 3%untranslated region (3%UTR) of messenger RNAs (mRNAs). MitomiRs are miRNAs of nuclear or mitochondrial origin that are localized in mitochondria and have a crucial role in regulation of mitochondrial function and metabolism. In eukaryotes, mitochondria are the major sites of oxidative metabolism of sugars, lipids, amino acids, and other bio-macromolecules. They are also the main sites of adenosine triphosphate (ATP) production. Conclusions. In the review, we discuss the role of mitomiRs in mitochondria and introduce currently well studied mito- miRs, their target genes and functions. We also discuss their role in cancer initiation and progression through the regu- lation of mRNA expression in mitochondria. MitomiRs directly target key molecules such as transporters or enzymes in cell metabolism and regulate several oncogenic signaling pathways. They also play an important role in the Warburg effect, which is vital for cancer cells to maintain their proliferative potential. In addition, we discuss how they indirectly upregulate hexokinase 2 (HK2), an enzyme involved in glucose phosphorylation, and thus may affect energy metabo- lism in breast cancer cells. In tumor tissues such as breast cancer and head and neck tumors, the expression of one of the mitomiRs (miR-210) correlates with hypoxia gene signatures, suggesting a direct link between mitomiR expression and hypoxia in cancer. The miR-17/92 cluster has been shown to act as a key factor in metabolic reprogramming of tumors by regulating glycolytic and mitochondrial metabolism. This cluster is deregulated in B-cell lymphomas, B-cell chronic lymphocytic leukemia, acute myeloid leukemia, and T-cell lymphomas, and is particularly overexpressed in several other cancers. Based on the current knowledge, we can conclude that there is a large number of miRNAs present in mitochondria, termed mitomiR, and that they are important regulators of mitochondrial function. Therefore, mitomiRs are important players in the metabolism of cancer cells, which need to be further investigated in order to develop a potential new therapies for cancer.
Keywords: cancer cell metabolism; microRNAs; mitochondria; mitomiR